Dietary sodium citrate supplementation enhances rehydration and recovery from rapid body mass loss in trained wrestlers - Timpmann, S.; Burk, A.; Medijainen, L.; Tamm, M.; Kreegipuu, K.; Vähi, M.; Unt, E.; Ööpik, V. (Applied Physiology, Nutrition, and Metabolism, 2012)
This study assessed the effects of dietary sodium citrate supplementation during a 16 h recovery from 5% rapid body mass loss (RBML) on physiological functions, affective state, and performance in trained wrestlers. Sixteen wrestlers performed an upper body intermittent sprint performance (UBISP) test under three conditions: before RBML, after RBML, and after a 16 h recovery from RBML. During recovery, the subjects ate a prescribed diet supplemented with sodium citrate (600 mg/kg; CIT group, N = 8) or placebo (PLC group, N = 8) and drank water ad libitum. RBML reduced (p < 0.05) UBISP mean power and increased urine specific gravity (USG). Reduction in mean power was associated with changes in plasma volume (PV) (r = 0.649, p = 0.006) and USG (r = -0.553, p = 0.026). During the 16 h recovery, increases in body mass (BM) and PV were greater (p < 0.05) in the CIT group than in the PLC group. BM gain was associated with water retention in the CIT group (r = 0.899, p = 0.002) but not in the PLC group (r = 0.335, p = 0.417). Blood pH, HCO3- concentration, and base excess increased (p < 0.05) only in the CIT group. Changes in UBISP, general negative affect, and general positive affect did not differ in the two groups. In conclusion, ingestion of sodium citrate increases blood buffering capacity and PV and stimulates BM regain during a 16 h recovery from RBML in trained wrestlers. However, sodium citrate does not improve UBISP nor does it have an impact on the affective state.